MAKNA TEOLOGI KEMATIAN UMAT HINDU DI BALI (KAJIAN TEKS YAMA PURWANA TATTWA) - I Made Pasek Subawa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Death is something that will definitely happen but it is uncertain when it will come. ForHindus death is the process of the soul's journey to Paramatman. So that the journey of the Atmadoes not have obstacles it needs to be assisted by carrying out the death ceremony, hereinafterreferred to as Pitra Yad. Pitra yadnya implementation is one way to break away from the tri tiesof citizens in order to achieve happiness now and happiness to come. The meaning of the deathceremony according to the Yama Purwana Tattwa Text is to accelerate the process of the unionof souls with paramatman. Through this understanding of theology of death it is hoped thatHindus can choose the desired form of death ceremony according to their preferred character,and even write a will to their families about the desired form of death ceremony in accordancewith their beliefs, even though in essence the titles of Brahma, Vishnu, Shiva or Mahadeva aredesignations for The almighty God, namely Brahman himself.